Assessment of the 11-year nationwide trend of out-of-hospital cardiac arrest cases among elderly patients in Japan (2005–2015). (October 2018) - Matsuyama, Tasuku; Kitamura, Tetsuhisa; Kiyohara, Kosuke; Kiguchi, Takeyuki; Kobayashi, Daisuke; Nishiyama, Chika; Iwami, Taku; Ohta, Bon
Abstract: Objective: Japan has one of the most rapidly aging societies worldwide. This study aimed to assess the long-term nationwide trend of out-of-hospital cardiac arrest (OHCA) cases among elderly patients in Japan. Methods: This prospective, nationwide observational study in Japan included elderly patients aged ≥65 years who experienced OHCA from January 1, 2005 to December 31, 2015. The patients were classified into three groups: young-old, aged 65–74 years; old-old, aged 75–84 years; and oldest-old, aged ≥85 years. The primary outcome of this study was one-month survival with a favorable neurological outcome, which was defined as a cerebral performance category scale score of 1 or 2. Results: A total of 877, 009 patients were included in our analysis. The number of elderly patients with OHCA increased from 65, 968 in 2005 to 87, 339 in 2015, and each age category showed a significantly increasing trend (p value <0.001 for each trend). The proportions of favorable neurological outcomes also increased from 1.2% in 2005 to 2.8% in 2015 in the young-old group; from 0.6% in 2005 to 1.1% in 2015 in the old-old group; and from 0.2% in 2005 to 0.5% in 2014 in the oldest-old group. Furthermore, this improving trend was notable for those with a shockable first documented rhythm. Conclusions: Based on this long-term nationwide observational study in Japan, the number of elderly patients with OHCA increased annually, and a significant improvement in the patients' neurological outcomes was noted regardless of age category, particularly among those with an initially shockable rhythm.